2002
DOI: 10.1126/science.1068452
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromas in NF1: Schwann Cell Origin and Role of Tumor Environment

Abstract: Neurofibromatosis type 1 (NF1) is one of the most prevalent dominantly inherited genetic diseases of the nervous system. NF1 encodes a tumor suppressor whose functional loss results in the development of benign neurofibromas that can progress to malignancy. Neurofibromas are complex tumors composed of axonal processes, Schwann cells, fibroblasts, perineurial cells, and mast cells. Through use of a conditional (cre/lox) allele, we show that loss of NF1 in the Schwann cell lineage is sufficient to generate tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
541
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(564 citation statements)
references
References 20 publications
16
541
1
6
Order By: Relevance
“…76 The current understanding of the key role of Schwann cells is based on studies with conditional knockout mice and the genetic analysis of cells cultured from human neurofibromas. 32,76,77 These studies have collectively shown that bi-allelic inactivation of the NF1 gene is a prerequisite for neurofibroma formation but that tumorigenesis can occur only in an NF1 ϩ/Ϫ background. Neurofibromas can be classified into two main categories: cutaneous and plexiform.…”
Section: Nf1 Lesions Caused By Loh or Somatic Second-hit Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…76 The current understanding of the key role of Schwann cells is based on studies with conditional knockout mice and the genetic analysis of cells cultured from human neurofibromas. 32,76,77 These studies have collectively shown that bi-allelic inactivation of the NF1 gene is a prerequisite for neurofibroma formation but that tumorigenesis can occur only in an NF1 ϩ/Ϫ background. Neurofibromas can be classified into two main categories: cutaneous and plexiform.…”
Section: Nf1 Lesions Caused By Loh or Somatic Second-hit Mutationsmentioning
confidence: 99%
“…The bi-allelic inactivation leading to the development of plexiform neurofibromas apparently takes place in embryonic cells that have the potential to generate large populations of cells carrying a single NF1 second-hit mutation. 77,81 The growth of plexiform neurofibromas during early childhood distinguishes these tumors from cutaneous neurofibromas, which are undetectable before puberty. 5 Mouse studies have demonstrated that Nf1 Ϫ/Ϫ Schwann cells are necessary, but not sufficient, for tumor formation to occur.…”
Section: Pathogenesis Of Plexiform Neurofibromasmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Schwann cell tumours caused by inherited mutations in the NF1 gene do not form in mouse models unless the surrounding stromal cells are at least heterozygous for the mutation. These tumours are highly populated with mast cells and it seems likely that a haploinsufficiency of NFI in these cells is the cause of the tumour formation (Zhu et al, 2002).…”
Section: Mast Cellsmentioning
confidence: 99%
“…It thus emerges that tumor progression requires complex interactions between Nf1 Ϫ/Ϫ Schwann cells and Nf1 ϩ/Ϫ cell lineages in the tumor microenvironment. 13 In this context, a recent study has shown that mouse Nf1 ϩ/Ϫ mast cells not only are recruited to neurofibromas from bone marrow but also that the neurofibromas fail to develop if the recruitment of the Nf1 ϩ/Ϫ cells is hindered, and the tumors begin to shrink when they are depleted of the Nf1 ϩ/Ϫ mast cells. 14 The present study points to the possible existence of yet another category of players in the development of cutaneous neurofibromas: multipotent NF1 ϩ/Ϫ precursor cells that can give rise to some of the different cell types found in neurofibromas.…”
mentioning
confidence: 99%